Reproductive Isolation Among Three Nocturnal Moth-Pollinated Sympatric Habenaria Species (Orchidaceae) - Zhang, Hai-Ping; Tao, Zhi-Bin; Trunschke, Judith; Shrestha, Mani; Scaccabarozzi, Daniela; Wang, Hong; Ren, Zong-Xin (Frontiers in Plant Science, 2022)
Comparison and quantification of multiple pre- and post-pollination barriers to interspecific hybridization are important to understand the factors promoting reproductive isolation. Such isolating factors have been studied recently in many flowering plant species which seek after the general roles and relative strengths of different pre- and post-pollination barriers. In this study, we quantified six isolating factors (ecogeographic isolation, phenological isolation, pollinator isolation, pollinia-pistil interactions, fruit production, and seed development) that could possibly be acting as reproductive barriers at different stages among three sympatric Habenaria species (H. limprichtii, H. davidii, and H. delavayi). These three species overlap geographically but occupy different microhabitats varying in soil water content. They were isolated through pollinator interactions both ethologically (pollinator preference) and mechanically (pollinia attachment site), but to a variable degree for different species pairs. Interspecific crosses between H. limprichtii and H. davidii result in high fruit set, and embryo development suggested weak post-pollination barriers, whereas bidirectional crosses of H. delavayi with either of the other two species fail to produce fruits. Our results revealed that pollinators were the most important isolating barrier including both ethological and mechanical mechanisms, to maintain the boundaries among these three sympatric Habenaria species. Our study also highlights the importance of a combination of pre-and post-pollination barriers for species co-existence in Orchidaceae.